Performance of polypyrrole coated metal oxide composite electrodes for benthic microbial fuel cell (BMFC). Issue 2 (April 2020) - Prakash, Om; Mungray, Alka; Chongdar, Shobhana; Kailasa, Suresh Kumar; Mungray, Arvind Kumar
Graphical abstract: Highlights: Coating of natural acceptors metal oxides on carbon felt was sucessfully achieved. Ppy coated MnO2 (MP), Fe2 O3 (FP) and MnO2- Fe2 O3 (MFP) nanocomposites were compared. Charge transfer resistance was less and kinetic activity was 409 times higher in FP. A plausible mechanism of electron conductivity was explained. Abstract: Low power output in benthic microbial fuel cells (BMFCs) hinders its stability into real utilization. Previous studies have examined on power enhancement by applying various metal oxides and other performance enhancing agents. However, an efficient option which improves the power production and also discourage the use of toxic compound to the marine ecosystem is still lagging in the scientific domain. Thus, the forgoing study compared the efficiency of natural electron acceptors through their individual performances and by combining them with a conductive polymer. The electrochemical performances of polypyrrole (PPy) coated MnO2 (MP), Fe2 O3 (FP) and MnO2- Fe2 O3 (MFP) nanocomposites were evaluated by modifying the surface of electrodes in benthic microbial fuel cells. Among these, FP exhibited higher power density (170 mW/m 2 ) than that of other MFP (117.29 mW/m 2 ), MP (90.54 mW/m 2 ) and unmodified electrodes (69.19 mW/m 2 ). The properties and performances of nanostructured modified anodes were studied by measuring their electrochemical behaviour and power generation capacity. The FP coated anode exhibited 409 times higher kinetic activity than control. The electrochemical performance and power density of benthic microbial fuel cell were greatly enhanced due to their high surface area, and the presence of rich electron donating functional groups and heteroatoms. These results demonstrate that the PPy coated MnO2, Fe2 O3 and MnO2- Fe2 O3 nanostructured materials act as promising benthic microbial fuel cells electrodes with a high degree of electrochemical activities and power densities.